2019
DOI: 10.1002/er.4856
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nano‐enhanced myristic acid using metal oxide nanoparticles for thermal energy storage

Abstract: Summary Fatty acids have been broadly used as phase change materials (PCMs) for thermal energy storage. However, low thermal conductivity limits their performances. This paper investigates the influence of metal oxide nanoparticle addition on myristic acid (MA) as nano‐enhanced PCM (NEPCM). Stability, chemical, and thermal properties were considered. Four types of nanoaprticles, TiO2, CuO, Al2O3, and ZnO, were dispersed in MA at 0.1, 0.5, 1, and 2 wt%. Stability and dispersion were checked by sediment photogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…13 Many researchers have extensively investigated enhanced TC of PCMs containing various nanostructured materials such as metallic nanoparticles, 14,15 carbon-based nanomaterials, [16][17][18] and oxide nanoparticles. [19][20][21] Table 1 demonstrates the list of some recent studies [22][23][24][25][26][27][28][29][30][31][32][33] on enhanced TC of PCMs with dispersed oxide nanoparticles and reports the TC enhancement for all nanoparticle loadings and temperatures. As shown in Table 1, some discrepancies can be found between various references due to materials, preparation methods, and measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many researchers have extensively investigated enhanced TC of PCMs containing various nanostructured materials such as metallic nanoparticles, 14,15 carbon-based nanomaterials, [16][17][18] and oxide nanoparticles. [19][20][21] Table 1 demonstrates the list of some recent studies [22][23][24][25][26][27][28][29][30][31][32][33] on enhanced TC of PCMs with dispersed oxide nanoparticles and reports the TC enhancement for all nanoparticle loadings and temperatures. As shown in Table 1, some discrepancies can be found between various references due to materials, preparation methods, and measurement techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The butyl stearate/multiwalled carbon nanotube (MWCNT) composite with a weight fraction of 0.02 was recommended for the TES systems. Ouikhalfan et al 20 experimentally explored the effects of metal oxide nanoparticles (TiO 2 , CuO, alumina, and ZnO) with the volume fractions lower than 0.02 on the melting/freezing of the myristic acid (MA). The thermal conductivity of the base PCM was escalated by 1.50, 1.49, 1.45, and 1.37 times when ZnO, Al 2 O 3 , CuO, and TiO 2 nanoparticles with the volume fraction of 0.02 were added, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain SI et al 19 prepared nanoencapsulated oleic acid‐PEG with LHS values for melting/solidification of 58.79/55.49 J/g and an encapsulation ratio of 52.12%. Ouikhalfan et al 35 added to CuO, Al 2 O 3 , TiO 2 , and ZnO nanoparticles to myristic acid as base PCM and reported that the fabricated composites showed good chemical and thermal stability after 500 melt‐freeze cycles. In a very recent experimental investigation, the dispersion stability of the TiO 2 ‐Ag nanoparticles in molten paraffin wax as PCM was studied using a surfactant agent, and they reported that TiO 2 ‐Ag nanocomposite had uniform dispersion and improved thermal properties 36 .…”
Section: Introductionmentioning
confidence: 99%